Wet-dry cycles enable the parallel origin of canonical and non-canonical nucleosides by continuous synthesis - Becker, Sidney; Schneider, Christina; Okamura, Hidenori; Crisp, Antony; Amatov, Tynchtyk; Dejmek, Milan; Carell, Thomas (Nature communications, 2018)
The molecules of life were created by a continuous physicochemical process on an early Earth. In this hadean environment, chemical transformations were driven by fluctuations of the naturally given physical parameters established for example by wet-dry cycles. These conditions might have allowed for the formation of (self)-replicating RNA as the fundamental biopolymer during chemical evolution. The question of how a complex multistep chemical synthesis of RNA building blocks was possible in such an environment remains unanswered. Here we report that geothermal fields could provide the right setup for establishing wet-dry cycles that allow for the synthesis of RNA nucleosides by continuous synthesis. Our model provides both the canonical and many ubiquitous non-canonical purine nucleosides in parallel by simple changes of physical parameters such as temperature, pH and concentration. The data show that modified nucleosides were potentially formed as competitor molecules. They could in this sense be considered as molecular fossils.
Keywords: evoluce chemická; biopolymery; molekulární struktura; Models, Chemical; Nucleosides; chemické modely; Origin of Life; původ života; Earth, Planet; Země (planeta); nukleosidy; Molecular Structure; Water; Biopolymers; Evolution, Chemical; RNA; voda